Overview of RPA technologies - A. Troianovska; Ye. Batrak; N. Tsopa (Adaptivni Sistemi Avtomatičnogo Upravlinnâ)
The article's focus is on RPA (Robotic Process Automation) technologies and how they affect businesses' operational procedures. RPA is a software technology that enables businesses to automate repetitive and boring processes with the use of built-in algorithms created by various RPA platforms and vendors. This article's objective is to examine, organize, and determine the potential futures for RPA deployment in the contemporary business environment. The article goes into great detail on the main advantages of RPA implementation into organization system, such as improving operations' productivity, efficiency, and accuracy; cutting down on job completion time; and minimizing errors. A lot of focus is placed in the article on the examination of RPA implementation's potential futures. It is anticipated that RPA's functionality and capacities will continue increasing over time, and that RPA will be integrated with a variety of cutting-edge technologies, elevating business process automation to new heights. In conclusion, the application of RPA technologies is a big step toward the optimization of business processes in a corporate environment that is changing quickly.